MicroRNA-29b/graphene oxide–polyethyleneglycol–polyethylenimine complex incorporated within chitosan hydrogel promotes osteogenesis - Qin, Han; Ji, Yujie; Li, Guangyue; Xu, Xiaohui; Zhang, Chuangwei; Zhong, Wenjie; Xu, Shihan; Yin, Yuanyuan; Song, Jinlin (Frontiers in Chemistry, 2022)
MicroRNAs (miRNAs) play a pivotal role in regulating a number of physiologic and pathologic processes including bone marrow mesenchymal stem cell osteogenic differentiation, making it a candidate used to promote osteogenesis. However, due to intrinsic structure and characteristics, “naked’’ miRNAs are unstable in serum and could not pass across cellular membrane. Nano delivery systems seem to be a solution to these issues. Recently, graphene oxide (GO) based nanomaterials is considered to be promising for gene delivery due to its unique physiochemical characteristics such as high surface area, biocompatibility, and easy modification. In this work, a GO based nanocomplex functionalized by polyethyleneglycol (PEG) and polyethylenimine (PEI) was prepared for loading and delivering miR-29b, which participates multiple steps of bone formation. The nanocomplex revealed good biocompatibility, miRNA loading capacity and transfection efficiency. miR-29b/GO-PEG-PEI nanocomplex was capsulated into chitosan hydrogel for osteogenesis. In vitro and in vivo evaluation indicated miR-29b/GO-PEG-PEI@CS composite hydrogel were able to promote BMSC osteogenic differentiation and bone regeneration. All these results indicates that PEG/PEI functionalized GO could serve as a promising candidate for miRNAs cellular delivery, and the miR-29b/GO-PEG-PEI@CS hydrogel is potential for repairing bone defect in vivo.